The values and principles of sustainable development in policy and legislation of the Republic of Poland - Wodzikowski, Czesław (Studia Ecologiae et Bioethicae, 2014)
Sustainable development can be variously translated and understood. !is stems primarily from the fact that this idea is sometimes presented differently in the literature. The article concerns the axiological system of sustainable development, how to interpret the idea of development, and the principles that lie at its core. Therefore, the idea of sustainable development in Poland has the rank of constitutional principle, its genesis in state politics and in the Polish legislation was also discussed.